2019
DOI: 10.1159/000500804
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Vision following Enzyme Replacement Therapy in a Patient with Mucopolysaccharidosis Type II, Hunter Syndrome

Abstract: We analyzed the effects of enzyme replacement therapy (ERT) on the visual acuity and visual fields of a patient with mucopolysaccharidosis type II, Hunter syndrome, with degeneration of the retina and abnormalities of the optic nerve. After the ERT, there was an improvement of the visual acuity and visual fields and an improvement of the activities of daily living. Despite the late onset of Hunter syndrome in this patient, ERT was still able to improve the visual function. We conclude that ERT should be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In accordance with previous results, we observed that most of these novelties were not assessed in subsequent clinical studies after five years from the publication of the case report [13]. Importantly, the new studies assessing these proposals were usually case reports [31,50,51,57,59,60]. Therefore, the evidence and innovations provided by case reports will take a long time to be incorporated into clinical studies on rare diseases [13].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In accordance with previous results, we observed that most of these novelties were not assessed in subsequent clinical studies after five years from the publication of the case report [13]. Importantly, the new studies assessing these proposals were usually case reports [31,50,51,57,59,60]. Therefore, the evidence and innovations provided by case reports will take a long time to be incorporated into clinical studies on rare diseases [13].…”
Section: Discussionsupporting
confidence: 86%
“…(3) Effects in pebbling skin lesions [26,27] Case report (Srinivas SM et al, 2017) [51] No clinical study after 8 years (4) Effects in hyperactivity, aggressive behavior, language functioning, and social interaction [28] No clinical study after 7 years No clinical study after 7 years [30,31] Case report Scarpa et al, 2017 Bonanni et al, 2014 [57,58] No clinical study after 8 years 7ERT effects in vision [32,33] Case report (Yamanishi R et al, 2019) [59] No clinical study after 5 years (8) ERT effect in autoimmune anemia, thrombocytopenia, or thrombocytopenic purpura [34,35] Case report (Alcántara-Ortigoza et al, 2016) [60] No clinical study after 8 years (9) Botulinum Toxin for the treatment of equinus deformity with an ERT [36] No new citations No clinical study after 8 years (10) ERT effects in involuntary movements (chorea) [37] No new citations No prospective study after 12 years (11) Early ERT effects in bone abnormalities [38] Cohort study (Manara R [39][40][41][42][43][44][45][46][47][48][49]. ** This study analyzed two novelties proposed by previous case reports.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…MPS II, or Hunter syndrome, is characterized by a deficiency of a lysosomal enzyme, iduronate-2sulfatase (I2S), that results in the deposition of HS and DS in lysosomes (20). MPS II is the only type of MPS that is X-linked recessive while the other types are autosomal recessive diseases.…”
Section: Mps II (Hunter Syndrome)mentioning
confidence: 99%
“…A case report headed by Yamanishi et al, has pointed out "salt and pepper" pigmentation of the RPE and reduced light sensibility of the retina with preservation of the visual-evoked potentials [87,88]. Optical coherence tomography (OCT) analysis mainly showed Accepted Article atrophy of the photoreceptors and RPE layers and, secondarily, an alteration of thickness of the ganglion cell layers and a mild raising of optic discs from the retina [88]. San Filippo syndrome, or MPS III, is the most common MPS class which results from defects in four different enzymes allowing classification into subtypes A-D.…”
Section: Rpe Phenotype In Lsdsmentioning
confidence: 99%